THE EFFECT OF SOCIAL FEEDBACK ON ARTISTIC CREATIVITY: A QUANTITATIVE STUDY OF FINE ARTS STUDENTS IN ENUGU STATE - Eheli, Anthony C. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Over the years, arts have assumed a ubiquitous part of humankind, reflecting a means of communicating ideas, feelings, and solutions in a way other than verbally or written. It is an area of study that requires skills and mental capabilities to be presented as a concept. Intimations suggest that the social environment influences creativity. Indeed, artistic ideas are created for appraisal. Hence, comments from people are integral to creative art. The primary objective of the current study was to examine the artistic creativity of fine art students based on social feedback. Participants in the study included one hundred and thirteen (n = 113) students enrolled in fine and applied art departments at tertiary institutions in Enugu State, Nigeria. Self-report measures were used to obtain data. The data were subjected to a simple linear regression analysis, which revealed a significant positive relationship between social feedback and artistic creativity. According to the study, social input is an essential component of artistic creation.